Recent Advances in Preoperative Cardiac Evaluation - Priebe, Hans-Joachim (Current Pharmaceutical Design, 2012)
Underlying cardiovascular disease is a potentially modifiable risk factor that contributes significantly to perioperative morbidity and mortality. Reducing perioperative and long-term morbidity and mortality requires risk modifying perioperative management. This, in turn, requires preoperative identification of patients with, or at risk of having cardiovascular disease. Preoperative cardiac evaluation includes, (i) recognition and treatment of active cardiac conditions, (ii) assessment of surgical risk, functional capacity, and clinical risk factors, (iii) identification of candidates for non-invasive cardiac testing, coronary angiography and preoperative coronary revascularization, and (iv) pharmacologic management. A cardiac risk assessment algorithm is useful in guiding systematic evaluation. Although preoperative cardiac evaluation has improved during the past decades, we are not yet in the situation where we can accurately predict individual perioperative risk because the individual stress response to a given stressor, and the individual interactions between pharmacological intervention and intra- and postoperative risk factors are highly variable. Furthermore, preoperative cardiac evaluation is only one aspect of overall perioperative care. There are numerous intra- and postoperative factors which have been shown to affect overall outcome. Not all of them can reliably be predicted or modified in a way which improves outcome. However, recognition of such factors and aggressive attempts at appropriate intervention may reduce overall risk more than preoperative evaluation in isolation. Without defining and subsequently targeting intra- and postoperative risk factors, the benefit of preoperative cardiac evaluation will be limited.
Keywords: preoperative; exercise test